The identity of the special education teachers in times of accountability policies - Fabián A. Inostroza (Arizona State University, 2020)
The main objective of this research is to understand the construction of the identity of special education teachers in the framework of the implementation of educational accountability policies in Chile. Methodologically, this study responds to the qualitative tradition of research, in which 10 special education teachers from the Metropolitan Region participated. The instruments to produce the information in this investigation correspond to the in-depth interview and the reflective log. As a technique for analyzing the narratives, the qualitative content analysis was used. Among the main findings is an identity construction in transformation and stressed by the demands of accountability and the production of standardization and exclusion practices as effects of the educational market logics, which go against the identity that historically these educators have built.